SIMULTANEOUS GEOPHYSICAL DATA INVERSION WITH USING PETROPHYSICAL PROPERTIES MODELING - Troinich, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Revised approach of joint inversion of geophysical data set carried out on the base of petrophysical properties modeling is proposed. Seismic and gravity data are recommended to be inversed. But proposed approach does not have any restrictions on using other geophysical methods (relation between geophysical parameters should exist). Inversion of seismic data is performed by using seismic tomography with ray approximation. The method is used to minimize mismatches between observed and estimated traveltimes. Gravity inversion is made by density distribution proportionally to cell influence on observation point in order to minimize mismatches between observed and estimated gravity in least squares sense. Simultaneous inversion of seismic and gravity data is possible only if functional relation between velocity and density exists. This relationship should be established with using petrophysical properties modeling. A petrophysical property modeling are performed by using method for multicomponent media. The main result of this paper is making of generalized scheme of lithological inversion via simultaneous inversion of seismic and gravity data and petrophysical modeling. The scheme could be treated as a set of independent problems of different nature. Each problem could be solved by various methods. A lot of other methods are widely known and their description might be found in scientific and technical publications. In this paper author describes only those methods which have been used for implementation of the proposed approach. The practical importance of described approach is a possibility to perform lithological inversion with taking into account all available geophysical and geological data. Inversion results are also satisfy all the geophysical data (inversion results of different geophysical data sets used separately could contradict each other).
Keywords: geophysical tomography; inversion; lithological inversion; modeling